2005
DOI: 10.5191/jiaee.2005.12101
|View full text |Cite
|
Sign up to set email alerts
|

Extension Agents’ Perceptions of Sustainable Agriculture in the Riyadh Region of Saudi Arabia

Abstract: Sustainable agriculture extension programs are mandated worldwide to foster the implementation of sustainable agriculture practices. These required sustainable agriculture extension programs are to be conducted by extension agents, therefore understanding extension agents' perceptions toward sustainable agriculture is especially important. This research identified the perceptions toward sustainable agriculture of agricultural extension agents in the Riyadh Region, Kingdom of Saudi Arabia. The findings show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 5 publications
3
20
0
Order By: Relevance
“…Positive perceptions or beliefs lead to specific intentions and attitudes that foster positive behavior (Knobloch & Martin, 2000). In the Middle East, studies revealed positive perceptions of extension professionals regarding the concept of sustainable agriculture (Chirazi et al, 2001;Al-Subaiee et al, 2005). In Iran, although wheat farmers of the Luresran Province did not perceive sustainable agricultural practices as effective farming practices for wheat production due to risks associated with those farming practices and lack of profitability, extension agents were of an opposite view (Chirazi et al, 2001 (Udoto & Flowers, 2001).…”
Section: The Perception Construct and Research Findings Regarding Permentioning
confidence: 99%
“…Positive perceptions or beliefs lead to specific intentions and attitudes that foster positive behavior (Knobloch & Martin, 2000). In the Middle East, studies revealed positive perceptions of extension professionals regarding the concept of sustainable agriculture (Chirazi et al, 2001;Al-Subaiee et al, 2005). In Iran, although wheat farmers of the Luresran Province did not perceive sustainable agricultural practices as effective farming practices for wheat production due to risks associated with those farming practices and lack of profitability, extension agents were of an opposite view (Chirazi et al, 2001 (Udoto & Flowers, 2001).…”
Section: The Perception Construct and Research Findings Regarding Permentioning
confidence: 99%
“…Over recent years, Saudi Arabia has experienced a rapid level of development. However, it has also faced the issue of limited natural resources, in particular, water, resulting in a reduction of its agricultural production (Al-Subaiee et al, 2005), with a negative impact on the agricultural sector and limiting the available food supply from local farms. However, a sustainable increase in agricultural production could be achieved by improving the productivity of the land and the use of water resources.…”
Section: Rational For Saudi Arabia Agricultural Ontology (Saaont)mentioning
confidence: 99%
“…The KSA government and the academic sector in the country then realized that the self-sufficiency policy was causing serious damage to Saudi Arabia's scarce groundwater resources (Al-Shayaa et al, 2012;Al-Subaiee, Yoder, & Thomson, 2005). The government decided to roll back its policy and in 2008 enacted a new policy that discouraged the cultivation of water-intensive crops such as wheat and encouraged the cultivation of high-value crops such as fruits and vegetables (Alabdulkader, Alamoud, & Awad, 2012;Al-Zahrani, 2010;Al-Zahrani & Baig, 2011;Ouda et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Soon after, the country realized that the self-sufficiency strategy that had led to agricultural over-production was taking place at the expense of over-exploiting groundwater resources. The unsustainable practice motivated the country to ban wheat exports and end subsidies to wheat farmers in 1993 (Al-Shayaa et al, 2012;Al-Subaiee et al, 2005;Elhadj, 2004). The ban of wheat exports caused a steep decline in wheat-cultivated area, wheat self-sufficiency and irrigation water demand, whilst the areas cultivated for vegetables, fruits and fodder crops continued to grow at a rate matching the increase of local market demand, as shown in Figures 1, 2 and 3.…”
mentioning
confidence: 98%